Game Puzzle Bangun Ruang 3d - Tri Indra Wijaya (Melek IT : Information Technology Journal, 2019)
Wake up space is a mathematical construct that has content or volume. Build space in mathematics is divided into several wake up space ie side, rib, and vertex. In learning to wake up the current space more use of wood media formed cubes, beams and others. Puzzle is a game that appeals to children because children are basically fond of interesting shapes and colors. In the early stages of knowing the puzzle, they may try to assemble an image or a puzzle by trying to install the puzzle parts. Game is one factor that is important in growing children. Utilization and use of educational games can support the learning process of children. With the educational game is expected to trigger the child to the spirit in learning and educational games can also be applied mainly to the cognitive aspect.